Quantifying Confidence. Issue 5 (6th November 2018) - Angeletos, George‐Marios; Collard, Fabrice; Dellas, Harris
Abstract : We develop a tractable method for augmenting macroeconomic models with autonomous variation in higher‐order beliefs. We use this to accommodate a certain type of waves of optimism and pessimism that can be interpreted as the product of frictional coordination and, unlike the one featured in the news literature, regards the short‐term economic outlook rather than the medium‐ to long‐run prospects. We show that this enrichment provides a parsimonious explanation of salient features of the data; it accounts for a significant fraction of the business‐cycle volatility in estimated models that allow for various competing structural shocks; and it captures a type of fluctuations that have a Keynesian flavor but do not rely on nominal rigidities.